Successful Thrombolysis despite Having an Incidental Unruptured Cerebral Aneurysm - Briosa e Gala, D (2014)
Purpose. To report a case of successful thrombolysis performed in a patient with an incidental unruptured intracranial aneurysm and review the literature. Case Report. Patient admitted for ischemic stroke due to left posterior cerebral artery occlusion, with an incidental right middle cerebral artery aneurysm, who underwent treatment with tissue plasminogen activator (rtPA) resulting in clinical improvement without complications. Conclusion. The presence of unruptured intracranial aneurysms is considered as a contraindication to thrombolysis, due to a potentially higher hemorrhagic risk of aneurysm rupture. Patients, otherwise, eligible for thrombolysis are usually excluded from receiving this emergent treatment, despite its potential benefits. A reevaluation of the strict exclusion criteria for thrombolysis in acute stroke patients should be considered.